Nanobiotechnology human health and the environment - Dhawan, Alok; Singh, Sanjay; Kumar, Ashutosh; Shanker, Rishi (Boca Raton, FL Taylor & Francis, 2018)
This book combines the contributions from the experts of material science, molecular biology, toxicology bio-organic and bio-inorganic chemistry, toxicologists and environmental and food technology etc. to fathom the full scope of current and future of developments in the area of Nanobiotechnology. This book can also be used as text book for graduate students as an essential reference material, and as an reading material for general readers having a curiosity in Nanobiotechnology.--Provided by publisher.
Contemporary developments in nanobiotechnology : applications, toxicity, sustainability and future perspective / Anubhav Kaphle, Navya PN, Hemant Kumar Daima -- Nanotheranostics : implication of nanotechnology in simultaneous diagnosis and therapy / Brahmeshwar Mishra, Ravi R. Patel -- Nanodevices for early diagnosis of cardiovascular disease : advances, challenges and way ahead / Alok Pandya, Madhuri Bollapalli -- Emerging trends in nanotechnology for diagnosis and therapy of lung cancer / Nanda Rohra, Manish Gore, Sathish Dyawanapelly, Mahesh Tambe, Ankit Gautam, Meghna Suvarna, Ratnesh Jain, Prajakta Dandekar -- Surface modification of nanomaterials for biomedical applications : strategies and recent advances / Ragini Singh, Sanjay Singh -- Nanoparticle contrast agents for medical imaging / Rabee Cheheltani, Johoon Kim, Pratap C. Naha, David P. Cormode -- Recapitulating tumor ECM : design criteria for developing 3D tumor models / Dhaval Kedaria, Rajesh Vasita -- Understanding the interaction of nanomaterials with living systems : tissue engineering / Shashi Singh -- Nanoparticles and the aquatic environment : application, impact and fate / Violet A Senapati, Ashutosh Kumar -- Iron nanoparticles for contaminated site remediation and environmental preservation / Adam Truskewycz, Sayali Patil, Andrew Ball, Ravi Shukla -- Solubility of nanoparticles and its relevance in nanotoxicity studies / Archini Paruthi, Superb K. Misra -- Nanotechnology in functional foods and their packaging / Satnam Singh, Shivendu Ranjan, Nandita Dasgupta, Chidambaram Ramalingam -- Use of nanotechnology as an antimicrobial tool in the food sector / María Ruiz-Rico, Édgar Pérez-Esteve, José M. Barat -- Interface considerations in the modelling of hierarchical biological structure
Includes bibliographical references and index.
Keywords: Nanotechnology -- Methods; Nanomedicine; Nanostructures